Constriction of carotid arteries by urokinase-type plasminogen activator requires catalytic activity and is independent of NH2-terminal domains - Massey, Philip G.; Tanaka, Shinji; Buckler, Joshua M.; Jiang, Bo; McCourtie, Anton; Qian, Kun; Tom, Clifford; Stempien-Otero, April; Wen, Shan; Luttrell, Ian; Chitaley, Kanchan; Dichek, David A. (Thrombosis and Haemostasis, 2009)
Urokinase-type plasminogen activator (uPA) is expressed at increased levels in stenotic, atherosclerotic human arteries. However, the biological roles of uPA in the artery wall are poorly understood. Previous studies associate uPA with both acute vasoconstriction and chronic vascular remodeling and attribute uPA-mediated vasoconstriction to the kringle – not the catalytic domain of uPA. We used an in-vivo uPA overexpression model to test the hypothesis that uPA-induced vasoconstriction is a reversible vasomotor process that can be prevented – and uPA fibrinolytic activity preserved – by: 1) removing the growth factor and kringle domains; or 2) anchoring uPA to the endothelial surface. To test this hypothesis we constructed adenoviral vectors that express: wild-type rabbit uPA (AduPA); a uPA mutant lacking the NH2-terminal growth-factor and kringle domains (Adu-PAdel); a mutant lacking catalytic activity (AduPAS→A), and a cell-surface anchored mutant (AdTMuPA). uPA mutants were expressed and characterised in vitro and in carotid arteries in vivo. uPAS→A had no plasminogen activator activity. Activity was similar for uPA and uPAdel, whereas AdTMuPA had only cell-associated activity. AduPAS→A arteries were not constricted. AduPA, AduPAdel, and AdTM-uPA arteries were constricted (approximately 30% smaller lumens; p≤0.008 vs. AdNull arteries). Papaverine reversed constriction of AduPA arteries. uPA-mediated arterial constriction is a vasomotor process that is mediated by uPA catalytic activity, not by the NH2-terminal domains. Anchoring uPA to the endothelial surface does not prevent vasoconstriction. uPA catalytic activity, generated by artery wall cells, may contribute to lumen loss in human arteries. Elimination of uPA vasoconstrictor activity requires concomitant loss of fibrinolytic activity.
Keywords: Gene therapy; gene transfer; vascular remodelling; endothelial cells; proteases